2017
DOI: 10.1161/jaha.117.006514
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Prognostic Utility of Left Ventricular Global Longitudinal Strain in Hypertrophic Obstructive Cardiomyopathy Patients and Preserved Left Ventricular Ejection Fraction

Abstract: BackgroundIn obstructive hypertrophic cardiomyopathy patients with preserved left ventricular (LV) ejection fraction, we sought to determine whether LV global longitudinal strain (LV‐GLS) provided incremental prognostic utility.Methods and ResultsWe studied 1019 patients with documented hypertrophic cardiomyopathy (mean age, 50±12 years; 63% men) evaluated at our center between 2001 and 2011. We excluded age <18 years, maximal LV outflow tract gradient <30 mm Hg, bundle branch block or atrial fibrillation, pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…However, 2D‐STI has been used to evaluate myocardial mechanics in HCM patients at rest rather than during exercise, which skews the ability to identify deformational mechanics in HCM patients. Although recent studies have demonstrated that LV global longitudinal strain (LVGLS) and systolic strain rate (SR) reserve are associated with poor prognosis despite normal LV ejection fraction, these studies overlooked the effects of LV diastolic function and its reserve on exercise capacity . Therefore, overall changes in LV mechanics and functional reserve, as well as their association with functional capacity in HCM patients, measured using exercise stress echocardiography and 2D‐STI have not been thoroughly evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…However, 2D‐STI has been used to evaluate myocardial mechanics in HCM patients at rest rather than during exercise, which skews the ability to identify deformational mechanics in HCM patients. Although recent studies have demonstrated that LV global longitudinal strain (LVGLS) and systolic strain rate (SR) reserve are associated with poor prognosis despite normal LV ejection fraction, these studies overlooked the effects of LV diastolic function and its reserve on exercise capacity . Therefore, overall changes in LV mechanics and functional reserve, as well as their association with functional capacity in HCM patients, measured using exercise stress echocardiography and 2D‐STI have not been thoroughly evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…GLS by speckle tracking is a sensitive parameter and its alteration occurs early in myocardial alteration process in comparison to increase of left ventricular volumes or LVEF [25]. Using a cut-off value of − 18% to define alteration of the GLS [26], which is associated with poor cardiac outcomes [27][28][29][30][31][32], we showed that Qa (using a threshold of 2250 mL/min) and Qa/CO (using a threshold of 33%) are the best tools to detect the early impact of vascular access flow on myocardium.…”
Section: Weak Impact Of the Avf On Cardiovascular Functional Parameters And Echocardiographic Findingsmentioning
confidence: 99%
“…However, the LV mass reduction does not necessarily lead to complete LV diastolic function improvement because LV mass decrease is slow and continues in a nonlinear fashion. The fibrotic component of the LV mass may take several years to regress after the TAVR and can even become permanent [ 14 , 19 , 20 ].…”
Section: Lvdd Improvement After Tavrmentioning
confidence: 99%
“…Controversial studies were reported about the impact of different degrees of PVR on outcomes after TAVR [ 31 , 40 ]. Sato et al found increased LVEDP among patients who died within 1 year after TAVR, and presence of post-TAVR aortic regurgitation was the only independent predictor of mortality at 1 year [ 20 ]. Halkin et al did not find any significant association between mild PVR and post-TAVR mortality, but moderate to severe PVR was shown to be an independent predictor of all-cause mortality at mid-term follow-up (30 months) [ 22 ].…”
Section: Impact Of Prosthesis-patient Mismatch and Aortic Regurgitatimentioning
confidence: 99%